Aristóteles, fuente principal del De principiis naturae - Rego, Thomas (Sapientia, 2006)
In this study we prove that the main source of St. Thomas Aquinas's De principiis naturae is Aristotle. The chosen method is an exhaustive linear comparison between the opuscule and three books of Aristotle —Physics A and B and Metaphysics A—. The search of the opuscule's sources in terms of subject matters, argumentations, expressions and even examples reveals how much is owed to Books A and B of Physics and, to a lesser extent, to Book A of Metaphysics of Aristotle. This study shows us that, on the one hand, De principiis naturae has been written up like a summary of the first two Books of Aristotle's Physics, omitting the critics to the old philosophers, but thus managing to make a presentation of the fundamental theses of the philosophy of the nature. On the other hand, we also show that to this summary St. Thomas has added a presentation of the analogy in the last chapter, being based on Metaphysics.